Study of drug prescription pattern in diarrhoea patients admitted to paediatric ward in a government tertiary care hospital in Maharashtra, India - Deshmukh, Vinod S.; Chube, Swapnil P. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: World Health Organization (WHO) has defined diarrhoea as, ‘the passage of loose stools by an individual, at least thrice a day or more frequently than normal’. It is most commonly caused by intestinal infection, mainly viral. Every year there are about 2 billion cases of diarrhoea worldwide, a second leading cause of mortality in children below the age of 5 years. WHO estimated that antibiotic treatment was necessary in only one in twenty cases of childhood diarrhoea. Yet huge resources are currently spent on anti-diarrhoeal drugs annually, most rendered useless or harmful. This study was proposed to evaluate the utilization pattern of drugs prescribed for diarrhoea in children, in a government tertiary care hospital in Maharashtra. Methods: This cross-sectional observational study was carried out in the paediatric ward of government tertiary care hospital, Maharashtra. All patients of age less than twelve years with diarrhoea admitted to paediatric ward within the study period of January 2015 - June 2016 were included in the study. Patients older than twelve years or admitted with other gastrointestinal diseases or co-mordbid conditions were excluded. Statistical analysis was done using descriptive statistics. Results: Majority of the patients admitted were males and more than half the patient population were in the age group of less than or equal to 3 years. Polypharmacy was found to be present in the prescribing pattern, with average, more than 4 drugs prescribed for diarrhoea treatment, in each prescription. Majority drugs were prescribed using brand names and parenteral route. Use of antibiotics was also found to be inappropriate in majority of the cases. Conclusions: The study highlighted the importance of drug utilisation studies and pointed out inappropriate drug prescribing trends for diarrhoea cases in a tertiary care hospital in Maharashtra.